Cost of Holding Excess Reserves: The Indian Experience - Abhijit Sen Gupta (Indian Council for Research on International Economic Relations (ICRIER), 2008)
Most of the existing literature has used single reserve adequacy measures to evaluate the volume of excess reserves. In this paper, we employ empirical methods to generate a comprehensive reserve adequacy measure, incorporating the various objectives of holding reserves, and compare the actual reserve accumulation experience of various emerging markets with the prediction of our empirical model. Using this comprehensive reserve adequacy measure, we calculate the cost of holding excess reserves for India by looking at three different alternative uses of resources. We find that India is foregoing as much as 2 of its GDP by accumulating reserves instead of employing resources in alternative uses.
Keywords: F37; F47; C33; 330; Reserve Holdings; Reserve Management; Währungsreserven; Geldpolitik; Schwellenländer; Indien; Vergleich; Welt